Event-triggered adaptive prescribed performance control of uncertain nonlinear systems with unknown control directions. (February 2021) - Zhao, Nan-Nan; Ouyang, Xin-Yu; Wu, Li-Bing; Shi, Feng-Rui
Abstract: The problem of event-triggered prescribed performance control for a class of uncertain nonlinear systems with unknown control directions and faults is investigated. Compared with the existing methods, a new set of error transformation functions is defined for the first time. Although no approximate structure is adopted, prescribed performance control (PPC) and event triggered control (ETC) are realized simultaneously for the nonlinear system considered in this paper for the first time. The proposed control scheme can guarantee that all closed-loop signals are bounded, and the tracking error, as well as all state errors, converges within the adjustable constraint functions. Finally, two simulation experiments verify the effectiveness of the proposed algorithm. Highlights: A new error transformation function is first proposed, and a new PPC is proposed. The proposed scheme can adapt to unknown actual and virtual control directions. Without using any approximation technique, ETC and PPC are realized simultaneously.